2022
DOI: 10.3389/fcell.2022.910626
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals the Difference in Human Normal and Degenerative Nucleus Pulposus Tissue Profiles and Cellular Interactions

Abstract: Background: The nucleus pulposus is a constituent structure of the human intervertebral disc, and its degeneration can cause intervertebral disc degeneration (IDD). However, the cellular and molecular mechanisms involved remain elusive.Methods: Through bioinformatics analysis, the single-cell transcriptome sequencing expression profiles of human normal nucleus pulposus (NNP) cells and human degenerative nucleus pulposus (DNP) cells were compared to clarify the transcriptome differential expression profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…But in C5, the expression of SERPINA1 was inverse, and the communication stayed in a low strength. Chondrocyte 4 (C4) is an inflamed chondrocyte ( Li et al, 2022 ), and SERPINA1 expressed abundantly in C4. Although there were few NPH cells in C4, the expression of SERPINA1 was much greater in NPH compared with NPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But in C5, the expression of SERPINA1 was inverse, and the communication stayed in a low strength. Chondrocyte 4 (C4) is an inflamed chondrocyte ( Li et al, 2022 ), and SERPINA1 expressed abundantly in C4. Although there were few NPH cells in C4, the expression of SERPINA1 was much greater in NPH compared with NPD.…”
Section: Discussionmentioning
confidence: 99%
“…GEO database entries for scRNA-seq GSE199866 ( Cherif et al, 2022 ) and GSE205535 ( Li et al, 2022 ) were downloaded. The R package Seurat ( https://satijalab.org/seurat/ ) was utilized to analyze scRNA-seq data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether KAN regulated one or more of them to exert energy metabolism reprogramming and anti-inflammation effect during IVDD is worthy to be explored. Thirdly, Li et al reported that nine cell types were identified in human normal nucleus pulposus (NNP) cells and human degenerative nucleus pulposus (DNP) by single-cell transcriptome sequencing [ 50 ]. According to the effect of PFKFB3 inhibition on ECs and OCs that had been proved in other research [ 20 , 23 ], the inhibitory role of KAN on ECs and macrophages in NP could be partly forecasted.…”
Section: Discussionmentioning
confidence: 99%
“…A chondral subcluster highly expressing fibrotic genes, including COL1A1, MMP13 and FOSL1, has been identified in human NPCs and only exists in degenerated tissues [64,65]. Fibroblast proliferation has been confirmed [29], and the proportion of fibro-chondrocytes gradually increases with the progression of degeneration [66]. Through analysis of a deposited scRNA-seq database, we identified one cluster of human NPCs highly expressing both YAP-and fibrosis-related genes, named fibro NPCs.…”
Section: Verteporfin Suppresses Yap/tead1-cyclin B1 Axis and Alleviat...mentioning
confidence: 95%